External beam radiation and high-dose-rate brachytherapy for elderly patients with gastroesophageal junction adenocarcinoma - Zhang, Wei; Wang, Qifeng; Li, Tao; Lv, Jiahua; Liu, Huiming; Jia, Xitang; Liu, Bo; Fan, Yu; Wang, Yi; Wang, Junchao; Wu, Lei; Lang, Jinyi (Journal of Contemporary Brachytherapy, 2017)
Purpose: The aim of this study was to retrospectively observe and analyze the long-term treatment outcomes of 96 elderly patients with gastroesophageal junction adenocarcinoma (GEJAC) who were treated with californium-252 (252Cf) neutron brachytherapy (NBT) in combination with external beam radiotherapy (EBRT) with or without chemotherapy. Material and methods: From January 2002 to November 2012, 96 patients with GEJAC underwent treatment. The total radiation dose to the reference point via NBT was 8-25 Gy-eq in 2 to 5 fractions, with 1 fraction per week. The total dose via EBRT was 40-54 Gy, which was delivered over a period of 4 to 5.5 weeks with normal fraction. Results: The median survival time for the 96 patients was 15.3 months, and the 1-, 2-, 3-, and 5-year rates of overall survival (OS) were 62.5%, 33.7%, 20.1%, and 7.9%, respectively. The 1-, 2-, 3-, and 5-year rates for local-regional control (LRC) were 78.7%, 57.9%, 41.8%, and 26.4%, respectively. The patients’ age was an independent factor that was significantly associated with OS (p = 0.006) and LRC (p = 0.0005), according to univariate analysis. The 3-year OS (LRC) was 31.9% (62.9%) for patients aged 70-74 years and 16.1% (19.5%) for patients aged ≥ 75 years. From the time of treatment completion to the development of local-regional recurrence or death, 5 (5.2%) patients experienced fistula and 7 (7.3%) experienced massive bleeding. Conclusions: The clinical data indicated that NBT in combination with EBRT produced favorable local control and long-term survival rates for elderly patients with GEJAC, and that the side effects were tolerable. The patient’s age could be used to select the appropriate treatment in an elderly patient.